A novel B–Si–Zr hybridized ceramizable phenolic resin and the thermal insulation properties of its fiber-reinforced composites. Issue 3 (1st February 2023) - Xin, Yi; Niu, Zhaoqi; Shen, Shuai; Ma, Xiaoyan; Chen, Fang; Wang, Luyao; Chen, Beixi; Wang, Chengzhi; Zhang, Chengshuang; Hou, Xiao
Abstract: A novel B–Si–Zr hybridized ceramicizable resin(BSZ-PR) was fabricated by chemical reaction of boric acid, zirconium hydroxyl-containing polyhedral oligomeric silsesquioxane(Zr-POSS) and phenolic. The incorporation of boric acid and Zr-POSS improved the thermal stability of the resin effectively, and the residual carbon rate increased to 72.63% at 800 °C under nitrogen atmosphere. The flexural strength of carbon fiber/BSZ-PR and high silica fiber/BSZ-PR composites were increased by 25.7% and 175.5%, and linear ablation rates were reduced by 37% and 44.75%, respectively. It was discovered that the ceramic structures such as SiO2, ZrO2 and SiC can be formed at high temperatures as well as under extreme ablative conditions from both BSZ-PR and its fiber-reinforced composites, which may be the key to the improved thermal, ablative properties.